The philosophic consultant : - Koestenbaum, Peter (Jossey-Bass/Pfeiffer, 2003)
The Philosophic Consultant redefines the way managers must think about their organizations, people and markets to be successful both in business and in life. It calls each of us to understand that ethics in life and in business may be your most important concerns. By helping the reader focus on implementation decisions, choices, and commitment, Peter Koestenbaum points the way for responsible and effective managements in a world where trust seems to be challenged on every front." —Otis W. Baskin, Ph.D., special advisor to the president and CEO of the Association for the Advancement of Collegiate School of Business, International, professor of management, and former dean, Graziadio School of Business Management, Pepperdine University